الفضيلة عند افلاطون - اوطيب فتيحة; اشراف: شرقي يونس (جامعة محمد بوضياف المسيلة, 2025)
الفضيلة عند أفلاطون ليست مجرد أخلاق نتعلمها، بل هي فنٌّ لتهذيب النفس وقيادتها نحو عالم الحقيقة، وليكون الإنسان فاضلاً، لابد أن يُحقق كل جزء أو فضيلة وظيفتها بتكامل الفضائل الأربع، فيقود العقل بالحكمة، وتحمى الروح بالشجاعة، والشهوة تطيع باعتدال، ليكلّل هذا الانسجام بالعدالة التي هيو تاج الفضائل. بالتالي، فالفضيلة ليست شيئا نولد به أو نكتسبه صدفة، بل هي شيء نتذكره من عالم المثل حين كانت النفس خالصة ونقية، والجميل في طرحه أن من يعرف الخير لا يسلك إلا سبيله، لأن الجهل أصل الشر (الرذائل). فالسعادة هي سعادة الروح التي تجد الأمان والمعرفة، ومن هنا لا عجب أن يجعل أفلاطون الفيلسوف حاكماً، لأنه قادر على فهم الفضيلة بتحقيقها في نفسه وفي المدينة. الكلمات المفتاحية: الفضيلة، الحكمة، النفس، الانسجام، العفّة، الشجاعة، العدالة. ABSTRACT: The virtue of Plato is not just ethics that we learn, but rather an art to refine the soul and its leadership towards the world of truth, so that a person is virtuous must achieve every part or virtue of its function with the complementarity of the four virtues, in the mind leads with wisdom, and the soul protects courage, and lust obey in moderation, to crown this harmony with justice that is the crown of virtues. Serendipity, but it is something that we remember from the world of the proverb when the soul was pure and pure, and it is beautiful in its proposal that whoever knows goodness can only take his way, because ignorance is the origin of evil (vices). Happiness is happiness that finds safety and knowledge, and from here it is no wonder that Plato makes the philosopher the ruler, because he is able to understand the virtue by achieving it in himself and in the city. Leave ourselves from the world of the body to the light of the mind and absolute good. KEYWORDS: Virtue, Wisdom, Soul, Harmony, Chastity, Courage, Justice.